Average oocyte quality index as a method for scoring dysmorphic oocytes in women with ovarian endometrioma undergoing in vitro fertilization and its correlation with ovarian reserve - Ju Hee Park; Seul Ki Kim; Byung Chul Jee (Clinical and Experimental Reproductive Medicine, 2026)
Objective: This study investigated whether the average oocyte quality index (AOQI), used as a dysmorphic oocyte scoring system, is higher in women with ovarian endometrioma than in those with unexplained infertility or diminished ovarian reserve (DOR).Methods: We included 92 intracytoplasmic sperm injection cycles in which one to five metaphase II oocytes were obtained, and the AOQI was calculated in each cycle. Cycles were grouped according to the indication for in vitro fertilization: current or recurrent endometrioma (34 cycles), unexplained infertility (26 cycles), and DOR (32 cycles). DOR was defined by a serum anti-Müllerian hormone (AMH) level